Produção e qualidade de sementes de sorgo sacarino em diferentes arranjos e épocas na região central do Rio Grande do Sul - Nunes, Silvia Cristina Paslauski (2015)
Global demand for biofuels/ethanol has increased in recent years, the sweet sorghum is a promising alternative for the increase of ethanol production. It's species of vigorous growth, short cycle, propagated by seeds and mechanizable culture. The evaluation of sowing dates and row spacing, for production of sweet sorghum seeds allows the characterization of the physiological quality and quantification of production. The objective is to bring information more efficiently in growing technologies for production of sweet sorghum seeds by sowing dates adjustment and line spacing as well as more responsive indication of cultivars for the conditions of the Central Region of Rio Grande do Sul. The research was conducted in the experimental area of the Department of Plant Science and analyzes of physiological quality were made in Didactic Laboratory and Research in seeds of the Federal University of Santa Maria in Santa Maria, RS. Were sown sorghum saccharine BR506, BR511, BR509 and Fepagro 19. On the following dates: first year 27/10/2012, 28/11/2012 and 18/12/2012 and the second year in 16/10/2013, 15/11/2013 and 16/12/2013 and in plots with five meters long, with four rows in the spacings of 0.42, 0.50 and 0.70 meters between rows, with four replications. All cultivars have potential for the production of seeds. The time factor is predominant for the production of seeds. Sowings of November and December were more promising for the production of quality seeds.